Improving Student Learning Outcomes through Project-Based Learning Models in Natural Science - Luthfi, Nurrana; Susanti, Ely; Avida, Avida; Sari, Pemi Purnama; Yonanda, Pramestry (Biosfer: Jurnal Tadris Biologi, 2024)
This research aims to improve the learning outcomes of fifth-grade students through a project-based learning model in natural and social science subjects. This research was classroom action research consisting of several stages: planning, implementation, observation, and reflection. The subject of this research was the fifth-grade students of State Elementary School. The instruments used were written tests and observations. All data were analyzed in a descriptive, quantitative, and qualitative manner. In the first cycle, the average score was 76.7, but students still needed management in collaboration to complete projects. In the second cycle, an average score of 87 was obtained, and students were able to build collaboration in completing the project. This activity is assisted by learning resources in the form of project worksheets, discussion sheets, posters, demonstration sheets, and free-choice enrichment sheet media for students. Based on the results of cycles I and II, it can be concluded that the improvement of student learning outcomes is influenced by a project-based learning model in which students can think critically, solve problems, pour out new ideas, be creative, actively interact, and communicate between groups.ABSTRAK: Tujuan penelitian ini untuk meningkatkan hasil belajar peserta didik kelas lima melalui model pembelajaran projek pada mata Pelajaran Ilmu pengetahuan alam dan social. Penelitian ini merupakan penelitian tindakan kelas yang terdiri dari beberapa tahapan, perencanaan, pelaksanaan,observasi dan refleksi. Subjek penelitian ini adalah peserta didik kelas lima SD Negeri. Instrumen yang digunakan tes tertulis dan observasi. Semua data dianalisis secara deskriptif kuantitatif kualitatif. Pada siklus I mencapai nilai rata-rata 76.7 akan tetapi peserta didik masih membutuhkan manajemen dalam kolaborasi menyelesaikan projek. Pada siklus II diperoleh nilai rata-rata 87 dan peserta didik mampu membangun kolaborasi dalam menyelesaikan projek. Aktivitas ini dibantu dengan sumber belajar berupa lembar kerja projek, lembar diskusi, poster, lembar demonstrasi, dan media lembar pengayaan bebas pilih bagi peserta didik. Berdasarkan hasil siklus I dan II dapat disimpulkan bahwa peningkatan hasil belajar peserta didik dipengaruhi oleh model pembelajaran berbasis proyek yang didalamnya peserta didik dapat berpikir kritis, memecahkan masalah, menuangkan ide-ide baru, berkreasi, aktif berinteraksi dan komunikasi antar kelompok.